Minimally invasive approach for percutaneous CentriMag right ventricular assist device support using a single PROTEKDuo Cannula - Kazui, Toshinobu (J Cardiothorac Surg, 2016)
BACKGROUND: Right ventricular failure is a serious complication after left ventricular assist device placement. CASE PRESENTATION: A 70-year-old male in decompensated heart failure with right ventricular failure after the placement of a left ventricular assist device. A single dual-lumen PROTEKDuo cannula was inserted percutaneously via the internal jugular vein to draw blood from the right atrium and return into the pulmonary artery using the CentriMag system, by passing the failing ventricle. The patient was successfully weaned from right ventricular assist device. CONCLUSIONS: In comparison to two-cannula conventional procedures, this right ventrivular assist device system improves patient rehabilitation and minimizes blood loss and risk of infection, while shortening procedure time and improving clinical outcomes in right ventricular failure.